2019
DOI: 10.1186/s12884-019-2441-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of vigorous intensity exercise in the third trimester of pregnancy: a systematic review and meta-analysis

Abstract: Background Fetal growth is dependent upon utero-placental vascular supply of oxygen and nutrients from the mother and has been proposed to be compromised by vigorous intensity exercise in the third trimester. The aim of this systematic review was to investigate the effects of vigorous intensity exercise performed throughout pregnancy, on infant and maternal outcomes. Methods Electronic searching of the PubMed, Medline, EMBASE, Cochrane Library, Web of Science and CINAHL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
65
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 63 publications
4
65
0
5
Order By: Relevance
“…Some of the research gaps identified for other populations remain especially relevant for pregnant women (e.g., the health benefits of breaking up sedentary time with bouts of light-intensity activity, or the joint association of physical activity and sedentary time with maternal and fetal health). On the other hand, although the myriad benefits of moderate-intensity physical activity during pregnancy and the postpartum period have been established [ 9 , 21 , 25 ], the safety and benefits of vigorous-intensity physical activity have been examined only recently [ 26 ]. Women who participate in vigorous physical activity on a regular basis before pregnancy may want to continue such activity for as long as possible throughout pregnancy and the post-partum period.…”
Section: Children and Adolescents (5–17 Years)mentioning
confidence: 99%
“…Some of the research gaps identified for other populations remain especially relevant for pregnant women (e.g., the health benefits of breaking up sedentary time with bouts of light-intensity activity, or the joint association of physical activity and sedentary time with maternal and fetal health). On the other hand, although the myriad benefits of moderate-intensity physical activity during pregnancy and the postpartum period have been established [ 9 , 21 , 25 ], the safety and benefits of vigorous-intensity physical activity have been examined only recently [ 26 ]. Women who participate in vigorous physical activity on a regular basis before pregnancy may want to continue such activity for as long as possible throughout pregnancy and the post-partum period.…”
Section: Children and Adolescents (5–17 Years)mentioning
confidence: 99%
“…Limited research has evaluated the effects of vigorous‐intensity exercise during pregnancy on maternal health and fitness outcomes. A recent systematic review and meta‐analysis suggested that for most women undergoing a healthy pregnancy without any contraindications, engaging in vigorous‐intensity exercise is safe and may not increase the risk for maternal and fetal health complications such as preterm delivery (Beetham et al, 2019). However, it must be noted that maternal fitness‐related outcomes were not assessed by Beetham et al (2019).…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta‐analysis suggested that for most women undergoing a healthy pregnancy without any contraindications, engaging in vigorous‐intensity exercise is safe and may not increase the risk for maternal and fetal health complications such as preterm delivery (Beetham et al, 2019). However, it must be noted that maternal fitness‐related outcomes were not assessed by Beetham et al (2019). Further inquiry, including high quality interventions and randomized controlled trials, are required to understand the effects of vigorous‐intensity exercise during pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that recommended levels of PA do not decrease the risk of CS (Lindqvist et al, 2016) or SGA (Pastorino et al, 2019), while others have found that exercise is associated with a decreased risk for CS (Di Mascio, Magro-Malosso, Saccone, Marhefka, & Berghella, 2016;Owe et al, 2016;Poyatos-Leon et al, 2015). Vigorous-intensity exercise in late pregnancy was not associated with an increased risk of SGA (Beetham et al, 2019).…”
Section: Backg Rou N Dmentioning
confidence: 95%
“…Notwithstanding, this study did not adjust for important confounders such as pregestational body mass index (BMI) and maternal complications during pregnancy. Systematic reviews showed that PA in late pregnancy was not associated with an increased risk of SGA, but exercise in the other trimesters of pregnancy and risk of SGA was less clear (Beetham et al, 2019;Bisson et al, 2016). Therefore, it…”
Section: Backg Rou N Dmentioning
confidence: 99%